DIRECT ELECTION OF THE HEAD OF REGIONAL URGENCY (DESCRIPTION OF THE IMPLEMENTATION OF THE THREE AUTONOMOUS REGIONS ACT) - Rahman, Abdul (Journal of Humanity, 2013)
A variety of problem and the political turmoil in some regions election last time appears in the event of a State feedback control Centre to the area. In the new order era regional chief election controversy cannot be released from the intervention Center. Usually the battles political elite in Jakarta imposes to the area. When the issue blew up in the area, Settlement is the effort, he brought the case to Jakarta. In accordance with the implementation, the Hall of the Central Government has a dominant power in the determination of the head region. Legislative involvement only in the process of being formalistic. It is seen clearly in Article 15 and 16 regarding the appointment of the head region, where only the legislative vote and the results presented at least two names for approval and/or designation from President to Governor, and Minister of the Interior for Regent and Mayor. The aegis of the Centre to all and sundry, who has strong access to the Centre, he will be the winner, either for political affairs, economy, law even though. The most votes is not a legislative guarantee of choice became the head of the area. The Center has the absolute power to determine the opposite although sound support. Conflicts often occur, regional Centre but ended with the defeat of the area